The frog prince and other fairy tales - Kelly; Miles (Essex Miles Kelly, 2015)
The Brothers Grimm The Frog Prince and other stories is a beautifully illustrated storybook for children aged 5+. Containing four famous favourites by master storytellers the Brothers Grimm, young readers will discover a world of imagination and adventure within. This book has a stunning sparkly cover, making it an ideal gift for fairy tale fans. Stories included: The Frog Prince, The Fisherman and His Wife, The Queen Bee, The Spindle, the Shuttle and the Needle.